2021
DOI: 10.1016/j.jvsv.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term phosphodiesterase-5 inhibitor use on refractory lymphatic malformations in adult and teen patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…7 The LMs of children treated with sildenafil for pulmonary hypertension improved significantly, and subsequent studies showed the treatment was effective in improving clinical symptoms, softening masses, and reducing the size of the lesions in patients with LMs. [8][9][10][11][12][13] In recent years, basic research has revealed that lymphatic endothelial cell (LEC) somatic gene mutations in LMs lead to persistent activation of the PI3K/AKT/mTOR pathway, which is an essential cause of developing LMs. Sirolimus, an inhibitor of mTOR, has been shown in numerous studies to significantly improve the imaging and clinical symptoms of patients with LMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The LMs of children treated with sildenafil for pulmonary hypertension improved significantly, and subsequent studies showed the treatment was effective in improving clinical symptoms, softening masses, and reducing the size of the lesions in patients with LMs. [8][9][10][11][12][13] In recent years, basic research has revealed that lymphatic endothelial cell (LEC) somatic gene mutations in LMs lead to persistent activation of the PI3K/AKT/mTOR pathway, which is an essential cause of developing LMs. Sirolimus, an inhibitor of mTOR, has been shown in numerous studies to significantly improve the imaging and clinical symptoms of patients with LMs.…”
Section: Introductionmentioning
confidence: 99%
“…The drug has been approved for the treatment of pulmonary hypertension in adults, and its application to LMs began in 2012 with a report published in the New England Journal of Medicine 7 . The LMs of children treated with sildenafil for pulmonary hypertension improved significantly, and subsequent studies showed the treatment was effective in improving clinical symptoms, softening masses, and reducing the size of the lesions in patients with LMs 8–13 . In recent years, basic research has revealed that lymphatic endothelial cell (LEC) somatic gene mutations in LMs lead to persistent activation of the PI3K/AKT/mTOR pathway, which is an essential cause of developing LMs.…”
Section: Introductionmentioning
confidence: 99%